2022
DOI: 10.1002/mabi.202200311
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Drug Delivery Systems for Eliminating Intracellular Bacteria

Abstract: The intracellular survival of pathogenic bacteria requires a range of survival strategies and virulence factors. These infections are a significant clinical challenge, wherein treatment frequently fails because of poor antibiotic penetration, stability, and retention in host cells. Drug delivery systems (DDSs) are promising tools to overcome these shortcomings and enhance the efficacy of antibiotic therapy. In this review, the classification and the mechanisms of intracellular bacterial persistence are elabora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 174 publications
0
7
0
Order By: Relevance
“…Endogenous stimuli-responsive systems are delivery strategies that take advantage of specific conditions within the TME or tumour cells, such as pH, enzymes, and redox, to enable stimuli-responsive targeted release of drugs, and then increase tumour specificity and reduce systemic adverse effects. 76–78 The use of antimicrobial nanomaterials as stimuli-responsive carriers can synergize with anticancer drugs to work together. 79 Among them, pH-responsive controlled release drug delivery systems are common.…”
Section: Drug Delivery Systems For Intra-tumoral Bacterial Therapymentioning
confidence: 99%
“…Endogenous stimuli-responsive systems are delivery strategies that take advantage of specific conditions within the TME or tumour cells, such as pH, enzymes, and redox, to enable stimuli-responsive targeted release of drugs, and then increase tumour specificity and reduce systemic adverse effects. 76–78 The use of antimicrobial nanomaterials as stimuli-responsive carriers can synergize with anticancer drugs to work together. 79 Among them, pH-responsive controlled release drug delivery systems are common.…”
Section: Drug Delivery Systems For Intra-tumoral Bacterial Therapymentioning
confidence: 99%
“…5,70 Further challenge is the severe side effects associated with an overly high dose required for therapeutic efficacy and the recurrent infection. 71,72 The development of efficient intracellular drug…”
Section: Antibiotic Delivery Systemsmentioning
confidence: 99%
“…5,70 Further challenge is the severe side effects associated with an overly high dose required for therapeutic efficacy and the recurrent infection. 71,72 The development of efficient intracellular drug delivery systems then emerged as a promising approach. 73 Significant amount of research has designed various antibiotic delivery systems and some of them have demonstrated good therapeutic efficacy for clinical translation.…”
Section: Antibiotic Delivery Systemsmentioning
confidence: 99%
“…Then, the resulting PF was further used as a micro-RAFT reagent, using A Boc and M OAc together as monomers to synthesize F(A Boc M OAc ) (Scheme S1, ESI †). 1 H NMR spectroscopy and GPC analysis showed that the molecular weights of PF and F(A Boc M OAc ) were B7069 (M w /M n = 1.34) and B11451 g mol À1 (M w /M n = 1.89), respectively (Fig. S1-S3, and Table S1, ESI †).…”
Section: Preparation Of F(am)-based Copolymer and Npsmentioning
confidence: 99%
“…Recurrent infections caused by intracellular bacteria have long been a difficult problem for human public health. 1 Bacteria persist in cells and induce latent infections that lead to diseases including osteomyelitis, sepsis, and necrotizing pneumonia. 2 Usually, treatment requires long-term and continuous drug action.…”
Section: Introductionmentioning
confidence: 99%